PHYSICAL FITNESS AND PHYSICAL SELF-PERCEPTION OF CHILDREN IN RELATION TO BMI: AN OBSERVATIONAL STUDY IN SOUTHERN ITALY - MONACIS, Domenico; PASCALI, Giacomo; ANNOSCIA, Sabrina; COLELLA, Dario (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2024)
Introduction. Despite international literature has well recognized the rule of physical education in primary school for the promotion of children’s educational process and the mediating effects on cognitive, emotional and social development, in many European countries sedentary lifestyles in children have increased involving all age groups and social classes. Moreover, in Italy the prevalence of children’s overweight and obesity is linked to increased physical inactivity and reduced opportunities for physical activity expenditure. The present study aims to assess physical fitness and self-perception in children involved in SBAM Project in Apulia (Southern Italy), according to gender and BMI. The assessment involved four physical fitness tests (SLJ, MBT, 10x4 and 6mWT) and a self-report to assess physical self-perception. A 3x2 ANOVA was carried out to assess the main and interaction effect of gender and BMI on considered variables. Results showed (a) better motor performances and self-perception in normal weight children compared to overweight and obese peers, (b) male were stronger and faster than female, and (c) physical self-perception didn’t change between obese male and female. Methodological interventions aimed at increasing time spent in motor activity and develop physical fitness are needed in primary school to promote health-oriented physical education. Received 2023 November 09; Revised 2024 January 04; Accepted 2024 January 05; Available online 2024 March 15; Available print 2024 March 15